Comparison of an oral and an intravenous feeding regimen in the newborn - Logan, R. W. (1974)
In a series of neonates undergoing comparable operations which did not affect the alimentary tract, the relative merits of similar oral and intravenous feeding regimens were compared. Metabolic balance studies were performed, together with measurement of plasma and urinary amino acids. Though the clinical response to both regimens was satisfactory, it was found that, in the group fed intravenously, certain of the plasma and urinary amino acids attained concentrations outside normal limits. This was almost certainly due to the nature of the amino acid solution infused.